Cellular damage and apoptosis along with changes in NF-kappa B expression were induced with contrast agent enhanced ultrasound in gastric cancer cells and hepatoma cells - Jiang Zao; Wu Wei; Qian Meng-lu (Cancer Cell International, 2012)
Abstract Background The effect of cell injury and apoptosis induced by ultrasound with contrast agent has been verified. Contrast agent enhanced apoptosis and expression of genes that related to apoptosis and are responsive to ultrasound. This effect was associated with reactive oxygen species (ROS) production induced by the sonochemical reaction, as reported in previous studies. NF-kappa B may be one of the factors involved in oxidizing reactions or modulation during the process of ultrasound inducing apoptosis. Results Ultrasound irradiated gastric cancer cells (SGC7901 cell line) and hepatocellular carcinoma cells (SMMC-771 cell line) cultured in medium containing contrast agent. Significant cellular damage and apoptosis were observed in the bath cells incubated for 24 hours following 120 seconds ultrasonic irradiation. I kappa B alfa expression synchronously increased in the treatment groups of both the cell lines, and the down-regulated expression of NF-kappa B influenced its-regulated expression of genes that related to apoptosis. Production of intracellular ROS and elevation of NF-kappa B level occurred after incubation of the cells for 1 hour following ultrasonic treatment. Conclusions Our result suggested that contrast agent enhanced the biological effect of ultrasound. Their reaction might stimulate the transitory expression of NF-kappaB, and subsequent elevation in IκBalfa expression could lead to the apoptosis of SGC7901 cells and SMMC-771 cells.